2020
DOI: 10.21037/cdt.2020.01.03
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of right ventricular deformation derived from cardiac magnetic resonance tissue tracking for all-cause mortality in light-chain amyloidosis patients

Abstract: Background: Early detection of right ventricular (RV) dysfunction is vital for determining the prognosis of light-chain amyloidosis (AL) patients. While few studies focused on RV deformation due to the limitation of research methods. The aim of this study was to determine the prognostic significance of RV myocardial strain in AL patients assessed by cardiac magnetic resonance (CMR) tissue tracking. Methods: Sixty-four AL patients (28 females and 36 males, mean age 58±12.8 years old; range 25-81 years old) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 39 publications
(38 reference statements)
1
23
0
Order By: Relevance
“…Similar results of the significant predictive value of RV free wall LS were found in patients with connective tissue diseases and patients with coronary artery disease [7,8]. Even though echocardiography remains the main imaging tool for RVLS assessment, cardiac magnetic resonance (CMR) became an important additional source of RVLG information in patients with different indications, primarily various CMPs [9][10][11]. These findings support the routine evaluation of RVLS in the majority of CV patients.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Similar results of the significant predictive value of RV free wall LS were found in patients with connective tissue diseases and patients with coronary artery disease [7,8]. Even though echocardiography remains the main imaging tool for RVLS assessment, cardiac magnetic resonance (CMR) became an important additional source of RVLG information in patients with different indications, primarily various CMPs [9][10][11]. These findings support the routine evaluation of RVLS in the majority of CV patients.…”
Section: Introductionsupporting
confidence: 59%
“…Multivariate analysis revealed only RVLS and RV LGE as independent predictors of overall mortality during follow-up [50]. A similar study reported not only that RV multidirectional strain (longitudinal, circumferential, and radial) could be used for discrimination between AL patients with and without cardiac involvement, but also between patients with normal and reduced RVEF and those with and without RV LGE [10]. RV LGE, RVLS, and radial strain were predictors of mortality in univariate analysis, but after adjustment for all RV and LV parameters, as well as for the stage of disease, only RV radial strain was an independent predictor of mortality [10].…”
Section: Amyloidosismentioning
confidence: 80%
See 1 more Smart Citation
“…The CMR tissue tracking technology that tracks features of the images and recognizes them in the contiguous image of the cine sequence can be used to quantitatively evaluate the displacement, motion function, and deformation of the myocardium in global or regional mode, particularly for the left ventricle (LV) and right ventricle (RV) (9,10). Of note, CMR deformation analysis has been shown to detect early abnormalities of the LV or RV contractile dysfunction beyond conventional global functional assessment with ejection fraction (EF) and provide prognostic information in some cardiovascular diseases (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Matched AL patients had worse LV diastolic function than Fabry cardiomyopathy, signi cant left ventricular systolic dysfunction was rare at early stages (17). MR imaging also plays an important role in the comprehensive evaluation of LV brosis (18-23).Moreover, cardiac MR tissue tracking is a feasible and valuable technique for the analysis of right ventricular deformation and could aid in the early diagnosis of right ventricle involvement in AL patients (24). T1 mapping may have the potential to detect a characteristic amyloid deposition with a decreasing gradient from base to apex (25).…”
Section: Ecg and Cardiac Imagingmentioning
confidence: 99%